Spliced leader RNA gene promoter sequence heterogeneity in CL-Brener Trypanosoma cruzi reference strain - Cribb, Pamela (2004)
Trypanosoma cruzi is divided into two phylogenetic lineages, T. cruzi I and T. cruzi II, which contain different spliced leader (SL) RNA gene promoter sequences: Class I SL gene promoter sequences are found in T. cruzi II, and Class II sequences in T. cruzi I. We analysed different SL RNA promoter sequences from CL-Brener reference strain, belonging to T. cruzi II lineage, and detected sequences that differed within the -80/+1 highly conserved region. Indeed, many of these divergent SL promoters present features of T. cruzi I promoters. Some of these sequences were grouped into the T. cruzi I sequences clade by Bayesian analysis. The results presented herein show that sequence heterogeneity in SL RNA gene promoter not only exists between T. cruzi strains but also within CL-Brener strain. These CL-Brener "T. cruzi I-like" sequences could be considered a molecular trace of a hybrid origin of the SL RNA gene and a new evidence for the presence of sequences of T. cruzi I origin into a T. cruzi II strain. The possible origins of these sequences are discussed.